2000
DOI: 10.1287/opre.48.4.578.12417
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Formulations for the Single-Airport Ground-Holding Problem with Banking Constraints

Abstract: Both the single-airport ground-holding problem (GH) and the multi-airport ground-holding problem can be extended by the addition of banking constraints to accommodate the hubbing operations of major airlines. These constraints enforce the desire of airlines to land certain groups of flights, called banks, within fixed time windows, thus preventing the propagation of delays throughout their entire operation. GH can be formulated as a transportation problem and readily solved. But in the presence of banking cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…Many other interesting papers on various aspects of optimizing ATFM and GHP appeared in the 1990s. Good reviews of the literature and of computational results can be found in Andreatta et al (1993) and Hoffman and Ball (2000).…”
Section: Air Traffic Flow Managementmentioning
confidence: 99%
“…Many other interesting papers on various aspects of optimizing ATFM and GHP appeared in the 1990s. Good reviews of the literature and of computational results can be found in Andreatta et al (1993) and Hoffman and Ball (2000).…”
Section: Air Traffic Flow Managementmentioning
confidence: 99%
“…This partitions each hour into arrival slots of equal time lengths (varying landing time requirements are ignored) which are then rationed to flights. The method for assigning landing time slots to flights is now based on the Collaborative Decision-Making (CDM) paradigm (see Hoffman et al 1999or Wambsqanss 1997. The CDM process involves substantial interaction between the airlines and the FAA.…”
Section: Application To the Ground-holding Problemmentioning
confidence: 99%
“…Similarly, departing flights from the hub to various destinations would also be scheduled soon after the arrival bank exchanges passengers and baggage among its flights. Richetta and Odoni (1993), Vranas et al (1994), Hoffman and Ball (2000). Various models, static vs dynamic, deterministic vs probabilistic, single-airport vs multi-airport have been well documented in the literature.…”
Section: Aircraft Holdingmentioning
confidence: 99%